A microanalysis of learner questions and tutor guidance in simulation‐assisted inquiry learning. (23rd December 2021) - Liu, Arita L.; Hajian, Shiva; Jain, Misha; Fukuda, Mari; Obaid, Teeba; Nesbit, John C.; Winne, Philip H.
Abstract: Background: Guidance during inquiry learning plays an important role in developing conceptual understanding and inquiry skills. This study analysed learner‐tutor interactions in a simulation‐assisted learning environment to investigate how tutor guidance enabled knowledge construction and fostered epistemic practice. Objectives: This research aimed to illuminate challenges learners encounter in the inquiry process and forms of guidance that support learning in both conceptual and epistemic aspects. Methods: This study uses a mixed methods approach. We analysed video recordings in which nine participants asked 72 questions and the microsequences of interactions immediately surrounding and including each question. We coded properties of each question and whether the tutors' utterances were intended to increase (upregulate) or decrease (downregulate) the complexity of the inquiry processes, and used a two‐step cluster analysis to explore groupings emerged from tutors' regulation guidance and learners' questions. Results and Conclusions: The regulatory intent of tutors' utterances depended on various characteristics of student questions. The microsequences clustered in five categories: 1) upregulated investigation and inference, 2) upregulated evidence‐based justification, 3) downregulated cognitive load, 4) downregulated procedural uncertainties, and 5) downregulated perceptual dissonance. Our findings suggest tutors offering guiding prompts should consider dual processes in the inquiry and, by strategically prompting them, strike a balance between the goals of guiding learners to discover scientific knowledge and grounding their conceptual understanding in concepts, data, and procedures. Implications: We emphasize conceptual and epistemic learning should be concurrently guided in scientific inquiry. We propose a bidirectional guidance model as a pedagogical approach to guide instructional practice. Lay Description: What is currently known about the subject matter: Rapid technological change urges schools to equip students with research and inquiry skills. Computer simulations provide an information‐rich environment for inquiry‐based learning. Guidance in inquiry learning is important for knowledge acquisition and the development of inquiry skills. What this paper adds: We illuminated challenges learners encounter in the inquiry learning process. We analysed forms of guidance that support learning in both conceptual and epistemic aspects. We identified dual processes involved in the inquiry process that have important implications. We proposed a bidirectional model for adaptive guidance in scientific inquiry. Implications of study findings for practitioners: Adaptive guidance facilitates conceptual and epistemic understanding by stimulating curiosity and reducing uncertainty in the inquiry process. Conceptual and epistemic learning need to be concurrently guided in scientific inquiry.